Effects of spring pasture burning, pasture deworming, and grain supplementation on performance of stocker steers grazing native Flinthills pasture - B.B. Barnhardt; J.C. Forcherio; R.R. Scott; Christopher D. Reinhardt; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2006)
A grazing study was conducted using 445 crossbred beef steers (496 lb) to determine the benefits of feeding a grain-based supplementon burned and unburned native pasture, with and without a Safe-Guard (fenbendazole) treatment while on pasture. Treatments consisted of mineral only, mineral with Safe-Guard treatment at day 29, and a supplement based on dry-rolled corn with a Safe-Guard treatment on day 29. All three treatments provided GainPro to the steers. Twelve pastures were used, six that were burned and six that were not burned during the month before the start of the trial. The control pastures were stocked at 272 lb per acre; the pastures with cattle receiving supplements were stocked at 312 lb per acre, 15% more than controls. Cattle grazing burned pastures had greater daily gains (1.81 vs. 1.65 lb/day; P=0.05) and gained 9 lb more per acre (85 vs. 76 lb/acre; P=0.03) than those grazing unburned pastures. Supplementation with grain mix improved the pounds of gain per acre, compared with cattle not receiving supplement (95 vs. 76 lb/acre; P<0.01). Steers treated with Safe-Guard while on pasture tended to have greater daily gains (1.73 vs. 1.61; P=0.17) and gained slightly more weight per acre, but this increase was not significant (P=0.24). Analysis of fecal samples indicated that deworming while on pasture did not reduce the average number of eggs shed per animal, but did increase the percentage of steers shedding no eggs.
Keywords: Cattlemen' s Day; 2006; Kansas Agricultural Experiment Station contribution; no. 06-205-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 959; Beef; Pasture burning; Pasture deworming; Steers